2018
DOI: 10.1007/s12032-018-1137-0
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy for castration-sensitive prostate cancer bone oligometastases

Abstract: To evaluate outcome in patients treated with stereotactic body radiotherapy (SBRT) on bone oligometastases from castration-sensitive prostate cancer after primary treatment. We retrospectively collected data of patients with less than five lesions at time of SBRT and hormone-naïve disease at the first extra-regional localization, treated between 03/2012 and 11/2016. Prostate-specific antigen (PSA) was measured every 3 months after SBRT. Imaging was performed in case of progression. Survival analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…No grade three or higher toxicities were reported by Decaestecker et al . (50 Gy in 10 fractions, 30 Gy in 3 fractions), Fanetti et al . (4–15 Gy in 1–5 fractions) or Ost et al .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…No grade three or higher toxicities were reported by Decaestecker et al . (50 Gy in 10 fractions, 30 Gy in 3 fractions), Fanetti et al . (4–15 Gy in 1–5 fractions) or Ost et al .…”
Section: Discussionmentioning
confidence: 65%
“…13 months for surveillance among men with up to three PCa oligometastases. In addition, several relatively small studies demonstrate the efficacy of metastasis‐directed radiotherapy to delay the clinical progression of oligometastatic PCa, with minimal adverse effects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been a surge in publications on PSMA‐PET/CT and SABR for oligometastatic PCa , only a few studies have reported the outcomes of SABR for PSMA‐PET/CT‐defined oligometastatic PCa (Table ) .…”
Section: Discussionmentioning
confidence: 99%
“…The advent of prostate‐specific membrane antigen (PSMA)‐PET/CT has allowed better detection of oligometastatic lesions in men with PCa . While there is an earlier study reporting on PSMA‐PET/CT‐guided conventional fractionated radiotherapy for oligometastatic disease , to our knowledge, published studies on the outcomes of PSMA PET/CT‐guided SABR for oligometastatic PCa are lacking .…”
Section: Introductionmentioning
confidence: 99%